(untitled) (Indonesian Economic Justice Review, 2024)
This paper explores the role of wealth redistribution policies in addressing income inequality in Indonesia. Despite consistent economic growth, Indonesia remains one of the most unequal countries in Southeast Asia, with significant disparities in wealth distribution between urban and rural areas, as well as between different ethnic and social groups. The paper critically analyzes the effectiveness of Indonesia’s wealth redistribution policies, such as progressive taxation, social welfare programs, and subsidies for education, healthcare, and housing. It evaluates the impact of these policies on reducing income inequality, particularly focusing on their ability to lift vulnerable populations out of poverty and promote economic mobility. The study uses a combination of national data and case studies to assess how various wealth redistribution mechanisms, such as direct cash transfers and subsidies, have impacted income distribution and social equity. The findings suggest that while wealth redistribution policies have made some progress in reducing poverty, they have not been sufficient to address the broader issue of income inequality. The paper concludes with recommendations for strengthening wealth redistribution efforts, including expanding social protection programs, reforming tax policies to ensure greater progressivity, and investing in programs that promote skills development and economic opportunities for disadvantaged communities.